Theories of Relational Health in Interpersonal Violence Research: A Scoping Review - Miller, Emily K.; Gillani, Braveheart; O’Donnell, Kari A. (Families in society, 2024)
Interpersonal violence is a pervasive public health problem that leads to emotional, behavioral, and physical health challenges. Theoretically, sound research examining protective factors, such as relational health, is imperative for developing effective interventions. However, the use of relational health theories in existing research needs to be better understood within the literature and should be further explored. Using scoping review methodology, 23 theories of relational health were identified in the research literature. Attachment theory and emotional security theory were the most frequently utilized. The remaining studies drew on a wide range of theories, including relational cultural theory, social support theories, and others. Findings highlight the complexities of relational experiences in interpersonal violence contexts. Future research should seek a more comprehensive understanding of the inclusion and application of relational health theories.